Mapping elementary students' understandings of the police - Andersson, Klas; Larsson, Kristoffer (JSSE - Journal of Social Science Education, 2024)
Highlights: – Research on conceptual change in civics is needed. – Phenomenography is useful for mapping different ways of understanding a particular concept, in this case, the different ways elementary students understand the police. – Civics teaching can benefit from mapping understandings of phenomena such as different social institutions. Purpose: Investigate first- to third-graders’ understandings of the police. Design/methodology/approach: Phenomenography is used to analyze elementary students’ understandings of the police as a social institution Findings: The results indicate three qualitatively different ways of understanding the police. The police as: attributes, activities and as a part of the democratic welfare state. Practical implications: Civics teaching that aims to develop students’ understandings of the police can benefit from taking the three different ways of understanding into consideration.